ORHAN DURU ÖYKÜLERİNDE YAPI VE İZLEK - BAYTİMUR, NAZLI MEMİŞ (Fırat Üniveristesi, 2012)
Türk yazınında öykü ve deneme yazarlığının yanında çeviri ve uyarlamalarıyla da tanınan Orhan Duru özellikle öykücü kimliğiyle ön plana çıkmıştır. Başlangıçta şiiri edebiyat algısına var etmeye çalışsa da bunda ısrarlı olmamıştır. Özellikle çağdaş problemler ve ruhsal daralmaların olduğu bir dönemde yaşaması öykülerine de doğrudan kaynaklık etmiştir. Duru öykücülüğünde dikkat çeken bir başka yön de dilsel tercihlerdir. Öykünün esas malzemesi gibi kullanılan bir dille karşılaşırız.Duru, Türk öykü geleneği içerisinde şiirde II. Yeni'nin yaptıklarına benzer bir tavır ve tarzı tercih etmiştir. Kendi kuşağının ve sonraki dönemlerin içinde veya yanında kalarak 1953'ten 2008'e kadar devam eden işlevsel bir yazma serüveni içerisinde olmuştur. Bu yönüyle öykümüzün değer katmanlarında önemli bir kalemdir.Anahtar Kelimeler : Orhan Duru, öykü, yapı, izlek.

Orhan Duru is known as both a short story author and an essay author in Turkish Literature. At the same time he realized translations and adaptations. But particularly he has been distinguished with telling story identity. At beginning he has tried to keep the poem at the fore plan but he has not insisted at this matter. He has lived in a period which is full with contemporary problems and psychological troubles. This diffuculty atmosphere has been directly the source of his stories. An another attracting attention point in the stories of Orhan Duru is his linguistic preferences. We meet a language using as the main material of story.In Turkish story tradition Duru has preferred a manner and style at poem resembling "II. Yeni" movement. He has become in an active writing adventure staying in and near his own generation and the later periods from 1950 to 2008. From this point of view he is an important writer in value layers of our story.Key Words : Orhan Duru, story, structure, theme.
The structure and theme in the stories of Orhan Duru
Keywords: Türk Dili ve Edebiyatı